Inuit (Ben, Jimmy, Harlan Smith) building snow houses, Cape Fullerton, Hudson Bay, Canadian Arctic - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1903)
A group of Inuit are building snow houses at Cape Fullerton, Hudson Bay, December 1903. Among them are three men identified as Ben, Jimmy, and Harlan Smith. The group appears to include at least two children. The bowsprit of the whaling schooner Era is visible at right. Infrastructure Lifestyle Title supplied by cataloger. Information from original envelope identifies this as Photo #198, #15. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.